2007
DOI: 10.3748/wjg.v13.i22.3128
|View full text |Cite
|
Sign up to set email alerts
|

Role of interventional therapy in hepatic artery stenosis and non-anastomosis bile duct stricture after orthotopic liver transplantation

Abstract: AIM:To analyze the clinical manifestations and the effectiveness of therapy in patients with orthotopic liver transplantation (OLT)-associated hepatic artery stenosis (HAS) and non-anastomosis bile duct stricture. METHODS:Nine cases were diagnosed as HAS and non-anastomosis bile duct stricture. Percutaneous transluminal angioplasty (PTA) was performed in four HAS cases, and expectant treatment in other five HAS cases; percutaneous transhepatic bile drainage, balloon dilation, stent placement were performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
1
12
1
Order By: Relevance
“…As a result, HAS needs to be treated before the development of significant biliary ischemia and graft dysfunction, which could adversely impact the clinical outcome. Percutaneous PTA is the primary therapeutic option for patients with HAS, and it ensures a good HA patency rate of 50%‐90% at 1 year . Though the role of underlying liver disease and the etiology of HAS were not explored in the present study, it is interesting to note that a quarter of the patients had FAP, and all 5 patients who underwent TACE later developed HAS.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As a result, HAS needs to be treated before the development of significant biliary ischemia and graft dysfunction, which could adversely impact the clinical outcome. Percutaneous PTA is the primary therapeutic option for patients with HAS, and it ensures a good HA patency rate of 50%‐90% at 1 year . Though the role of underlying liver disease and the etiology of HAS were not explored in the present study, it is interesting to note that a quarter of the patients had FAP, and all 5 patients who underwent TACE later developed HAS.…”
Section: Discussionmentioning
confidence: 87%
“…Abbasoglu et al established the need to treat HAS by demonstrating that the patients with HAS were twice as likely to develop biliary complications when compared to those without HAS. Zhao et al reported that PTA significantly improved survival in patients with HAS. Pulitano et al in a recent review suggested that PTA is not warranted in late‐onset HAS and asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Close surveillance is essential to identify HAS postoperatively, because if left untreated, HAS has up to a 65% chance of progressing to HAT #6 months. 11 Zhao et al 12 showed prolonged patient survival of 17 to 30 months in patients who received treatment for HAS compared with patients undergoing expectant management.…”
mentioning
confidence: 99%